ETR 300 : I.N.D.A.H Academy Fashion Collection / Nurizwan Zainal Ariffin ... [et al.] - Zainal Ariffin, Nurizwan; Md Rejab, Noorfazila; Abdullah, Zuraidah; Md Amran, Nor Mauzura (2002)
I.N.D.A.H Academy Fashion Collection is a final idea of four partners whom has been interested with this nature of business. focusing on Muslimah fashion and attire, we aim to serve all Muslim women with the latest and variety of fashion in the market by not neglecting their status and title as Muslimah. The products of our company are not only baju kurung's but it also covers all types of scarves, dresses, blouses and uniform. The textile used in this business grade from the cheapest to the most expensive type of textile. I.N.D.A.H Academy Fashion Collection also provides a place for newcomers learn how to sew. The certificate is required by agreement. The business also aims to fulfill the market needs, which by our observations lack of Muslimah fashion. In this modern era, Islamic fashions are not only limited to baju kurung's and chasuble only but also it has been expanding wider and more creative. The establishment of I.N.D.A.H Academy Fashion Collection is hoped to fill the needs and requirements of all Muslimah that are fashionable especially working woman and youth. Our mission is also to provide all Muslimah with the kind of fashion they need and at the same time following the guidelines and are subjected to Islam and it's Syariah.